Study the quality of life and anxiety in patients with myasthenia (clinical-parachlinal comparison) - Kalbus, Oleksandr (ScienceRise: Medical Science, 2018)
Aim of the research: To investigate the level of anxiety in adult patients with myasthenia. Materials and methods. An in-depth clinical-neurological, immunological (detection of antibodies to acetylcholine and / or muscle-specific tyrosine kinase receptors) examination, testing according to MGQoL-15 scale, and Spielberg-Khanin anxiety scale of 96 patients (56 women and 40 men) with myasthenia (71 - with generalized, 25 - with an ophthalmologic form, respectively) were done. Results. Antibodies to acetylcholine receptors were detected in 57 (80.3 %) of 71 patients with generalized form and in 13 (52 %) of 25 patients with ophthalmic myasthenia, antibodies to muscle-specific tyrosine kinase in 6 (8.5 %) of 71 patients with generalized form. In the case of an ophthalmic form, these antibodies were not detected. In 8 (11.3 %) out of 71 patients with generalized myasthenia and in 12 (48.0 %) out of 25 patients with ophthalmic form of myasthenia antibodies to acetylcholine receptors and muscle-specific tyrosine kinase were not detected. When the MGQoL-15 scale was used, the average quality of life was 10.34 ± 9.4 points (ranging from 0 to 31). In assessing of situational anxiety, a moderate level of anxiety was detected in 44 patients, high – in 24 patients, while the low level of anxiety had 28 people. Patients with an ophthalmic form of myasthenia (class I by MGFA) are significantly more likely to have a low level of anxiety (p <0.05). The moderate level of situational anxiety was significantly more frequently recorded in patients with myasthenia class III by MGFA (moderate form), and high level - in patients with myasthenia class IV by MGFA (expressed form). In patients with a low level of situational anxiety, the average duration of the disease was significantly lower (p <0.05). When comparing the quality of life in patients with myasthenia with the MGQoL-15 scale and the level of situational anxiety with the Spielberg-Khanin scale, there was a significant negative impact of increased anxiety on quality of life (r = -0.24, p = 0.01) Conclusions. The quality of life of patients with myasthenia and the level of anxiety disorders do not depend on the immunological subtype of the disease. The quality of life of patients with myasthenia is largely dependent on the degree of clinical manifestations of the disease. The increased level of situational anxiety reliably reduces the quality of life